PENGARUH TEKNIK RELAKSASI BENSON DAN MUROTTAL AL-QUR’AN TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI PRIMER - Laras ' Pratiwi; Yesi ' Hasneli; Juniar ' Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this research was to determine the effect of benson relaxation technique and murottal Al-Qur’an on blood pressure among patient with primary hypertension. The design was a quasy experiment research with non-equivalent control group. The research was conducted to patient with primary hypertension in the “Puskesmas Harapan Raya”. The number of 30 sample respondents was obtained by purposive sampling technique who classified into 2 groups of 15 people as experimental group and the 15 people as control group. This research used digital tensimeter. The data analyzed by using dependent t-test and independent t-test. This result showed that blood pressure sistole diastole values before and after providing intervention in the experimental group, p value sistole = 0,000 and p value diastole = 0,001 which meant that there was effect of benson relaxation technique and murottal Al-Qur’an on blood pressure to patient with primary hypertension. The result is expected of benson relaxation technique and murottal Al-Qur’an can be a nursing intervention to decrease blood pressure to patient with primary hypertension. Key words: Benson relaxation technique, blood pressure, murottal Al-Qur’an, primary hypertension Reference: 80 (2000 – 2014)